Evaluating toxicity impacts of environmental exposed chromium on small Indian mongoose (Urva auropunctatus) hematological, biochemical and histopathological functioning. (November 2020) - Andleeb, Shaista; Ahmad, Zulfiqar; Mahmood, Tariq; Bao, Shenxu; Arif Saeed, Abdullah; Jha, Sunil Kumar
Abstract: Sub-lethal toxic impacts of chromium on hematological, biochemical and histological parameters were analyzed in the female small Indian mongoose ( Urva auropuctatus) residing contaminated environment of tannery industry. Chromium bioaccumulation in the blood, liver and kidney tissue of the exposed mongooses was found elevated compared to the control mongooses' tissues. Total body weight (75.7%), liver weight (83.6%) as well as HSI (68.1%), RSI (86.2%) and the platelets counts (59.7%) were found significantly elevated, with significantly reduced RBCs (59.6%), and WBCs (64%). LFT and RFT were also found abnormal, moreover, the histopathological injuries had been distinct inside the kidney (>75%) and hepatic (>75%) tissues of exposed animals. Shrinkage and vacuolization (>75%) inside the hepatocyte expanded sinusoidal spaces and nuclear pyknosis (>75%) was evident within the hepatic tissue. Hypertrophy of epithelial cells of renal tubules and inter-renal cells of the head kidney with a reduction in tubular lumens (>75%) and vacuolization of tubules were witnessed within the kidney section. Atrophy inside the kidney inter-renal cells, glomeruli compression within the Bowman's capsules (>75%) following the necrosis in hematopoietic tissues were found in exposed animals. The present findings indicate that chronic exposure to chromium induces severe anemia, decreased serum protein concentration, hepatic and renal tissue histopathology, impairing the vital capabilities of liver, metabolic regulation, excretion, and stress homeostasis maintenance of which within the long-run may posture a severe risk to animal well-being then distress their inhabitants. Graphical abstract: Image 1 Highlights: High concentration of chromium was observed in tissues of small Indian mongoose. Body and organ weights as well as HSI and RSI were significantly changed. RBC, WBC and Hgb was significantly reduced while PLT were significantly increased. LFT (Liver function test) and RFT (Kidney Function test) were found abnormal. Histopathological lesions found in liver and kidney tissues.